GE_GERICHTE C/21009/2016 vom 28. Februar 2019 - GE Cour de justice (2019)
BAIL À LOYER;QUALITÉ POUR AGIR ET RECOURIR;DIMINUTION DE LOYER;RENDEMENT ABUSIF;FARDEAU DE LA PREUVE | CPC.70.al1; CO.270a.al1; CO.269; CPC.318.al1.letb